2020
DOI: 10.1088/1361-6463/abaced
|View full text |Cite
|
Sign up to set email alerts
|

Active metamaterials and metadevices: a review

Abstract: Metamaterials, as artificially structured materials composed of subwavelength arrays of resonant unit cells, can exhibit exotic properties beyond those accessible to natural materials. They were initially proposed for challenging fundamental laws and demonstrating negative refraction in the microwave regime, and subsequently exploited as a versatile platform to manipulate electromagnetic waves throughout the spectrum via their extreme scalability. Over the past decade, research into metamaterials has been exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
167
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(167 citation statements)
references
References 351 publications
0
167
0
Order By: Relevance
“…Metamaterial is a kind of composite material with an artificial structure [22][23][24]. With the development of metamaterials, researchers have found that the concept of metamaterials can be used to design superconductors and a metamaterial superconductor can exhibit a higher T C [25][26][27][28][29][30]. In 2007, our group doped inorganic electroluminescence (EL) material in a superconductor to increase T C via EL.…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterial is a kind of composite material with an artificial structure [22][23][24]. With the development of metamaterials, researchers have found that the concept of metamaterials can be used to design superconductors and a metamaterial superconductor can exhibit a higher T C [25][26][27][28][29][30]. In 2007, our group doped inorganic electroluminescence (EL) material in a superconductor to increase T C via EL.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility to increase the resonance Q-factor is to introduce a magnetic material in the sensing structure and to utilize the magneto-optical measurements of the transverse magneto-optical Kerr effect (TMOKE) instead of optical reflectance spectra [ 5 , 19 , 20 , 21 , 22 ]. The magneto-optical response can be enhanced with a variety of metamaterials [ 23 , 24 , 25 , 26 ], plasmonic coatings, dielectric nanostructures [ 27 , 28 , 29 ], and photonic crystals [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the trends of metamaterial research have progressed toward the realization of particular functions by constructing customized metasurfaces to control its optical properties [1][2][3][4][5], thereby creating extraordinary opportunities in the field of various functional devices like modulators, absorbers, and sensors [6][7][8][9]. Recently, researchers have shown an increased interest in the electromagnetically induced transparency (EIT) phenomenon in metamaterials, which is actually a quantum interference effect that forms a narrow transparent window within a broad absorption spectral region in multiple-level atomic systems [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%